Is virulence phenotype evolution driven exclusively by Lr gene deployment in French Puccinia triticina populations?. (23rd June 2022) - Fontyn, Cécilia; Zippert, Anne‐Catherine; Delestre, Ghislain; Marcel, Thierry C.; Suffert, Frédéric; Goyeau, Henriette
Abstract: Puccinia triticina is a highly damaging wheat pathogen. The efficacy of leaf rust control by genetic resistance is mitigated by the adaptive capacity of the pathogen, expressed as changes in its virulence combinations (pathotypes). An extensive P . triticina population survey has been carried out in France over the last 30 years, describing the evolutionary dynamics of this pathogen in response to cultivar deployment. We analysed the data set for the 2006–2016 period to determine the relationship between the Lr genes in the cultivars and virulence in the pathotypes. Rust populations were dominated by a small number of pathotypes, with variations in most of the virulence frequencies related to the corresponding Lr gene frequencies in the cultivated landscape. Furthermore, the emergence and spread of a new virulence matched the introduction and use of the corresponding Lr gene ( Lr28 ), confirming that the deployment of qualitative resistance genes is an essential driver of evolution in P . triticina populations. However, principal component analysis (PCA) revealed that certain pathotype–cultivar associations cannot be explained solely by the distribution of Lr genes in the landscape. This conclusion is supported by the predominance of a few pathotypes on some cultivars, with the persistence of several other compatible pathotypes at low frequencies. Specific interactions are not, therefore, sufficient to explain the distribution of virulence in rust populations. The hypothesis that quantitative interactions between P . triticina populations and bread wheat cultivars—based on differences in aggressiveness—is also a driver of changes in pathotype frequencies deserves further investigation. Abstract : Although several compatible virulence phenotypes were sampled from cultivars, only 1 or 2 phenotypes remained strongly dominant, suggesting that a quantitative host–pathogen interaction might also lead their population dynamics.